Study of fetomaternal outcomes in antepartum haemorrhage at tertiary care centre - Ghanchibhai, Faaizah Husain; Goyal, Sharda; Sharma, Nalini; Pargee, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Antepartum haemorrhage (APH) is a challenge to obstetrician as it involves a question of life and death to mother and fetus. Antepartum hemorrhage is the 2nd most common cause of maternal mortality and morbidity as sepsis and obstructed labour has decreased now. The aim of the study is to find the prevalence of APH. And to study foeto-maternal outcomes in patients with antepartum haemorrhage, association of comorbidities and risk factors. Methods: This study was conducted at Geetanjali Medical College and Hospital, Udaipur after obtaining approval from institutional research ethical board and written informed consent during the period of February 2019 to July 2020. This was prospective observational study, sample size was 60 patients. All the APH patients who were admitted at GMCH Obstetrics and Gynaecology department after 28 weeks of gestation were included in study. Extrauterine or bleeding due to general pathology was excluded. Total number of delivery were 1900 in above duration and number of APH patients were 60, so our incidence is 3.1%. Results: Total number of delivery were 1900 in above duration and number of APH patients were 60, so our incidence is 3.1%. According to maternal complications rate, It was 66.66 % in abruptio placenta, 37.03 % in placenta previa and jointly 53.33%. In placenta previa group 100% patients discharged with good GC, In abruptio placenta group 96.96% patients discharged with good GC and 3.04% patients discharged with poor GC. Perinatal mortality was zero in placenta previa group and in abruptio placenta, it was 27.27% (24.24% IUD, 3.03% neonatal death). Conclusions: The main cause of APH was abruption which was seen in 33 (55%) of patients and placenta previa was seen in 27 (45%) of patients. Maternal and neonatal complications, both were very high in abruption group as compared to placenta previa group. Overall maternal mortality rate was 53.33% and perinatal mortality rate was zero in placenta previa group while in abruption placenta group, it was 27.27%. There was no maternal complications in booked placenta previa cases only there were very few complications in emergency cases. In abruptio placenta group also complications were more in emergency cases, irregular booked and uncontrolled pregnancy pathology cases.